Analisis Sell in May and Go Away di Bursa Efek Indonesia dan Malaysia Periode 2017-2019 - Laila Marta Zarika; R.A. Sista Paramita (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
In May and Go Away (SMGA), Sell is a type of seasonal Anomaly, which historically originated in Europe and America that between May-October returns lower than the other periods from November to April. This research aims to determine the difference in abnormal return in the May-October (Worst period) period and November-April (Best period) in Indonesia and Malaysia Stock Exchange between 2017 to 2019. This test conducted using the company's stock price data samples listed on the LQ45 index in the Indonesia Stock Exchange and the FBMKLCI index in the Malaysia Stock Exchange period 2017 to 2019. Hypothesis testing using paired sample t-test to answer if there is a difference in return between the best period and the worst period, to prove the Sell's existence in May and Go Away. The results showed no difference returns between the best and worst periods in the Sell in May and Go Away phenomenon at the Indonesia and Malaysia Stock Exchange period 2017 to 2019. The Investor considers SMGA as not a phenomenon containing excellent or bad information that is capable of affecting the price movement of shares so that SMGA as a strategy to buy stocks in the best period and sell in the worst period is no longer relevant